2007
DOI: 10.1123/apaq.24.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sport Participation on the Basketball Skills and Physical Self of Adolescents with Conduct Disorders

Abstract: The purpose of this study was to examine the long-term effects of sport participation on the basketball skills and physical self-concept of adolescents with conduct disorders (CD). Participants were 24 adolescent males with CD, divided equally into three groups: (a) interestablishment basketball (IEBB), (b) integrated scholastic basketball (ISBB), and (c) control-adapted physical activity (APA). The basketball skills tests and physical self-concept were both administrated 4 times over an 18-month period. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…Although a number of studies were randomised controlled trials (Basile et al, 1995;Goodway & Rudisill, 1996;Minor & Elrod, 1994;Palermo et al, 2006), only one study described the process of randomisation (Basile et al, 1995). Six studies used quasi-experimental designs (Bloemhoff, 2006;Bonnette et al, 2001;Cross, 2002;Green et al, 2000;Maiano et al, 2007;Robinson et al, 2009). None of the studies reported power calculations to determine if their studies were adequately powered to detect their hypothesised effects.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a number of studies were randomised controlled trials (Basile et al, 1995;Goodway & Rudisill, 1996;Minor & Elrod, 1994;Palermo et al, 2006), only one study described the process of randomisation (Basile et al, 1995). Six studies used quasi-experimental designs (Bloemhoff, 2006;Bonnette et al, 2001;Cross, 2002;Green et al, 2000;Maiano et al, 2007;Robinson et al, 2009). None of the studies reported power calculations to determine if their studies were adequately powered to detect their hypothesised effects.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Additional benefits were identified by Palermo et al (2006) who found that a 10-month karate programme helped to improve temperament in children with social cognitive and disruptive behaviours. Two sport-based programmes targeting at-risk adolescent boys (Bonnette et al, 2001) and adolescent boys with conduct disorders (Maiano et al, 2007) did not significantly improve physical self-perceptions. Basile et al (1995) compared the effects of a skillmastery intervention to a fitness programme and a no treatment control and found that neither programme significantly improved self-concept in children with behavioural disorders.…”
Section: Sport and Skill-based Programmesmentioning
confidence: 99%
See 1 more Smart Citation
“…O engajamento de crianças com deficiência em atividades físicas tem por objetivo promover a saúde e a funcionalidade [1][2][3][4][5] , por meio de ganhos motores, emocionais e sociais 1,[6][7][8][9] . Especificamente para crianças e jovens com paralisia cerebral (PC), a prática de atividades físicas pode acarretar diversos benefícios, como melhora da força muscular 10,11 , capacidade aeróbica 11,12 e anaeróbica 12,13 , e possibilidade de experimentação de novos movimentos 6,12 .…”
Section: Introductionunclassified
“…[1][2][3][4] Araştırmacılar, fiziksel benlik algısının adölesan ve çocuklarda tutum bozukluğu, travma sonrası stres bozukluğu, anoreksiya nervoza, depresyon ve anksiyete gibi psikiyatrik rahatsızlıkların başlaması ve devamlılığında önemli bir etken olduğunu ortaya koymuştur. [5][6][7][8] Olumlu fiziksel benlik algısı, beden imajının geliştirilmesi, fiziksel aktivitelerden daha fazla keyif alınması ve sedanter davranışların azaltılmasında psikolojik ve fiziksel açıdan önemlidir. 9 Shavelson ve ark.nın ortaya koyduğu çok yönlü hiyerarşik modelde yer alan fiziksel benlik algısı, bireylerin psikomotor boyutta kendilerini değerlendirmesi olarak tanımlanmakta ve psikolojik sağlığın önemli bir göstergesi olarak ele alınmaktadır.…”
unclassified